2013
DOI: 10.1149/05009.0673ecst
|View full text |Cite
|
Sign up to set email alerts
|

Phonon Dispersion in <100> Si Nanowire Covered with SiO2 Film Calculated by Molecular Dynamics Simulation

Abstract: The phonon dispersion relation in <100> Si nanowire (SiNW) is calculated by employing a realistic atomistic model surrounded by thin SiO 2 layers. We performed molecular dynamics simulation to calculate the dynamical structure factor by the space-time Fourier transform of atomic trajectories, and extracted the phonon dispersion relations. Although the bulk dispersion relations are maintained in the SiNWs on the whole, acoustic phonon branches are diffused beyond recognition, which is considered as the origin o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In the our previous work, we focus on a wave number component of k = (2π/a)(q,0,0) for 0 < q < 1, because the nanowire model has a periodicity along only the <100> ECS Transactions, 75 (8) 785-794 (2016) direction (12,16). Here a = 5.43 Å, the side length of the conventional cubic cell of the Si lattice.…”
Section: Calculation Of Phonon Frequency and Phonon Dispersionmentioning
confidence: 99%
“…In the our previous work, we focus on a wave number component of k = (2π/a)(q,0,0) for 0 < q < 1, because the nanowire model has a periodicity along only the <100> ECS Transactions, 75 (8) 785-794 (2016) direction (12,16). Here a = 5.43 Å, the side length of the conventional cubic cell of the Si lattice.…”
Section: Calculation Of Phonon Frequency and Phonon Dispersionmentioning
confidence: 99%
“…Recently, some researchers have reported that a decrease in thermal conductivity is caused by disorder strain induced in the SiO 2 /SiNW interface by molecular dynamics (MD) simulation. [17][18][19] Moreover, Refs. 20, 21 have reported that electrical transconductance of SiNW is enhanced by oxideinduced strain.…”
Section: Introductionmentioning
confidence: 99%
“…11,12) In addition, Zushi and coworkers have shown that a decrease in κ is caused by the disorder strain induced in SiO 2 =Si NWs by molecular dynamics (MD) simulation. [13][14][15] From these findings, to realize Si NW devices with high electric and thermoelectric performance characteristics, further improvements through the optimization of strain in the nanowires covered with an oxide film, as well as size, impurity, and crystallinity, are necessary to achieve a higher mobility and a lower κ. However, it is difficult to evaluate strain accurately during nanoscale wire fabrication by various complicated processes.…”
Section: Introductionmentioning
confidence: 99%